P3-S3.08 Sensitivity and specificity of rapid HIV testing in a community setting. (10th July 2011) - Trottier, B; Nguyen, V K; Thomas, R; Machouf, N; Vezina, S; O'Brien, R; Lavoie, S; Longpré, D; Boissonnault, M; Charest, L
Abstract : Background: It was estimated in 2005 that 13% of men who have sex with men (MSM) in Montréal were HIV-positive, and that 23% of these were not aware of their diagnosis. Clinique l'Actuel introduced a pilot rapid HIV testing program using the MedMira kit in 2008. The objective of this study was to describe the sensitivity and specificity of rapid HIV tests in a community based, high HIV risk setting. Methods: An advertising campaign encouraged MSM and others at risk for HIV to undergo testing through dedicated clinics offering rapid HIV tests. Patients calling for testing deemed at high risk were given appointments within 2 weeks, where they filled out a short questionnaire, received medical consultation routine STI screening, pre- and post- test counselling and their HIV test results within the hour. Those consenting received with a MedMira or and INSTI rapid test and regular HIV screening. Any positive result was confirmed by Western blot. Results: 2500 individuals were tested: 98% men with a median age of 34 (IQR: 26–41). For the MedMira test there were 43 true positives, 2295 true negatives, 13 false positives and four false negatives. 145 patients received the finger-prick INSTI test giving two true positives and 143 true negatives. For MedMira, sensitivity was 91.5% and specificity 99.5% while both figures were 100% for INSTI. The four false negatives were also negative by standard ELISA but positive for P24 antigen. Patients testing positive for HIV had significantly more history of previous STI than those testing negative (p=0.041). Conclusion: In this setting sensitivity and specificity of the rapid tests used was comparable to standard testing. Acute seroconversion likely explains the four false negatives. As with conventional testing, rapid testing requires adequate counselling about the possibilities of a false negative test. In high-risk populations, routine STI screening should always be performed together with HIV screening.